Performance Analysis of Yoruba Traditional Beliefs in Lekan Balogun's Oya (Goddess of whirlwind): Art and Cultural Perspectives - Emmanuel Godwin Kalu; Babatunde Covenant Olugbenga; Kareeem Kolawole Ganiyu (Britain International for Academic Research (BIAR-Publisher), 2025)
This study explores the interplay of art and cultural dynamics in the Yoruba cosmology, performance analysis of Yoruba traditional beliefs in Lekan Balogun's Oya: Goddess of the whirlwind play. It examines how Oya, Ogun, Sango and Orunmila as deities materialize Yoruba cultural identity and shared values through rituals, myths, incantations, songs, dances, and symbols. Using a qualitative participatory observation method, the research hinges on Richard Schechner's Performance Theory (2003) and Oludanmini Ogunnaike's Yoruba Epistemology (2010) as theoretical frameworks. The research points to the Yoruba universe's dominance in shaping early beliefs, highlighting its central position in ensuring spiritual continuity and social integrity. The research reaffirms the dynamism of Yoruba society, as postulated by Edward B. Tylor, and its adaptability in contemporary pieces of art. Recommendations include further exploring Yoruba performance in the contemporary setting and keeping traditions orally alive to preserve cultural heritage.